"Collaboration, Conflict and Control: The 4th Workshop on Open Source Software Engineering" W8S Workshop - 26th International C 2004
DOI: 10.1049/ic:20040261
|View full text |Cite
|
Sign up to set email alerts
|

Towards a portfolio of FLOSS project success measures

Abstract: Project success is one of the most widely used dependent variables in information systems research. However, conventional measures of project success are difficult to apply to Free/Libre Open Source Software projects. In this paper, we present an analysis of four measures of success applied to SourceForge projects: number of members of the extended development community, project activity, bug fixing time and number of downloads. We argue that these four measures provide different insights into the collaboratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 5 publications
0
40
0
2
Order By: Relevance
“…Gaim has emerged as a more effective project, based on Crowston et al's multivariate measure of effectiveness in FLOSS contexts [3]. Evidence of Gaim's success can also be seen in that the project is still on-going, while Fire ceased active development in early 2007.…”
Section: Methodsmentioning
confidence: 99%
“…Gaim has emerged as a more effective project, based on Crowston et al's multivariate measure of effectiveness in FLOSS contexts [3]. Evidence of Gaim's success can also be seen in that the project is still on-going, while Fire ceased active development in early 2007.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review has demonstrated that there is a wide range of measures of project success. The field has not settled on any one measure, or a matrix of measures (Crowston, Annabi, Howison, & Masango, 2005). Some of the possible measures include: lines of code per programmer per year (Mockus et al, 2000), speed in closing bugs or trackers items (Stewart & Gosian, 2006), or modularity of source code (Shaikh and Cornford, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, how to mitigate the productivity impact of distributed work has become a key concern in methods literature FLOSSD differs from traditional software engineering in its transparency (Scacchi et al 2006), lack of formal SDMs, PMFs, budgets, schedules or rule structures (Scacchi 2007;Scacchi et al 2006), developer self-assignment of tasks (Crowston et al 2007) and success measures (Crowston et al 2004;Crowston et al 2006). For example, Crowston et al (2006) FLOSSD projects are organized into layers -a small group of core developers, a larger group of ad hoc developers who make minor changes and bug fixes and an even larger group who report problems (Mockus et al 2002).…”
Section: The Scope Of the Design Agentmentioning
confidence: 99%